Comparison of performances between partial double-pass and full double-pass systems in two-stage L-band EDFA - Md Samsuri, N.; Harun, S. W.; Ahmad, H. (2004)
The two-stage L-band EDFA with partial double-pass (DP) system is compared with the full DP system. The partial DP system has a higher gain and lower noise figure at small input signal power compared with the full DP system. The small signal gain and noise figure are obtained at about 31.2 dB and 6.2 dB, respectively, for the partial DP system. The reduction of gain in full DP system is due to the double-propagation of conventional-band amplified spontaneous emission in the short length erbium-doped fiber at the first stage that causes gain-clamping effect to the system. The higher gain in the partial DP system contributes to the lower noise figure even compared with single-pass two-stage system at small input signal powers. However, at high input signal powers, the lowest noise figure is observed for the single-pass system.